2022
DOI: 10.1186/s12879-021-06987-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of sexually transmitted infections among methamphetamine users in Eastern China: a cross-sectional study

Abstract: Background The reported incidence of sexually transmitted infections (STIs) in China has been increasing over the last decades, especially among drug users, which has become one of the main burdens of public health in China. This study was conducted to estimate the prevalence and associated factors of STIs among non-injecting methamphetamine (MA) users in Eastern China. Methods A cross-sectional survey was conducted among 632 MA users in Eastern Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Substance use can be linked to high-risk sexual behaviors, contributing to the spread of syphilis. For instance, studies conducted in 2021 showed that 60% of methamphetamine users reported engaging in unprotected sexual practices in a recent period [36][37][38].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Substance use can be linked to high-risk sexual behaviors, contributing to the spread of syphilis. For instance, studies conducted in 2021 showed that 60% of methamphetamine users reported engaging in unprotected sexual practices in a recent period [36][37][38].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Treponema pallidum , Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and HPV are the most common sexually transmitted pathogens in the United States, and their incidence rate increased by 30% to 60% from 2015 to 2019 [ 127 ]. Coinfection of HIV, HPV, and other STIs such as NG or Mycoplasma genitalium (MG) is common [ 128 ], and the risk of contracting an STI is increased according to the number of sexual partners [ 129 ], condomless receptive anal intercourse [ 130 ] and drug consumption [ 131 ].…”
Section: Sexually Transmitted Infections and Hpv And Hivmentioning
confidence: 99%
“…Conversely, it has been recognized that the decrease in the use of contraceptive methods, little fear of contracting an STI (including HIV), change in sexual behavior, lack of timely medical care, and the isolation of N. gonorrhoeae strains resistant to antibiotics are causes that favor the increase in cases of UG [10]. Lastly, cross-sectional surveys in developed countries have identified other risk factors in the acquisition of STIs, e.g., the use of drugs such as noninjectable methamphetamines [11].…”
Section: Introductionmentioning
confidence: 99%